KAJIAN PRODUKSI TEPUNG ATC (ALKALI TREATMENT CARRAGEENAN) DI TINGKAT PETANI RUMPUT LAUT DENGAN MENGGUNAKAN PELARUT KOH - Indah Kusumaningrum; Ony Linda (UHAMKA PRESS, 2017)
Seaweed is a biological resource that many found in Indonesia. The use of seaweed in Indonesiaas a source of food is still limited. While seaweed has a bioactive compound that is very benefcialfor health. Seaweed processing among seaweed farmers is still very limited. So far, seaweedfarmers process seaweed into dry form only, not yet made into semi-fnished products. Thepurpose of this research was to learn how to extract seaweed that can be applied at the level ofseaweed farmers to produce ATC (alkali treatment carrageenan) which contains fber, calcium,and natural iodine. The extracting solution used was KOH with concentrations of 6%, 7%, and8%. The yield of ATC (alkali treatment carrageenan) obtained from seaweed extraction processwith 8% KOH yields the highest yield (32,5%), ash 12,03%, carbohydrate 24,93%, and calcium927,15 mg / l. The extraction of seaweed with KOH 6% yields the highest crude fber (23,62%)and iodine 8,36%.